The Influence of Digital Marketing and Product Quality on Rocket Chicken Consumer Satisfaction Cirebon City - Albert Faber; Rezaldy Al Rahman; Lis Tatin Hernidatiatin (Universitas KH. Abdul Chalim Mojokerto, 2025)
Purpose of this study is to investigate how customer satisfaction at Rocket Chicken in Cirebon City is impacted by digital marketing and product quality. A quantitative research approach was employed, with data collected through an online questionnaire (Google Form) distributed to 349 respondents who had purchased Rocket Chicken products at least twice within the past three months. SPSS 25 software was used to help analyze data using multiple linear regression. Results reveal that: (1) Digital marketing has a significant impact on consumer satisfaction (β = 0.37; p < 0.05), especially through advertising on social media and website optimization, although the inaccuracy of promo information needs to be fixed; (2) Product quality has a more dominant influence (β = 0.59; p <0.05) with the main indicators of freshness, presentation, and consistency of taste; (3) Simultaneously, both variables explain 78% of the variation in consumer satisfaction (R² = 0.78). The practical implications of this study emphasize the need for Rocket Chicken to improve the consistency of product quality through strict operational standards, improve digital information management, and optimize interactions on digital platforms. These findings form the basis of a business strategy to increase consumer loyalty and competitiveness in the culinary industry in Cirebon City.